Changes of Antioxidant Activity and Physicochemical Components before and after Mixed Microbial Fermentation - Zhao Yumeng (BIO Web of Conferences)
Mixed microorganisms are the main strains to produce probiotics, and at present, the evaluation of probiotic function of mixed microorganisms is mostly focused on living bacteria, in view of the gradual decrease in the number of living bacteria in the process of production and storage, attention has been paid to the development of metabiotics including dead bacteria and their metabolites. However, there are few studies on how to improve the probiotic function after fermentation. In this paper, free radical scavenging experiment and NCM460 oxidative damage model of intestinal epithelial cells were used to evaluate in detail the antioxidant capacity of five mixed microorganisms and their descendants, to screen Lactobacillus plantarum with excellent antioxidant activity and to mine its functional genes, and to study the enhancement of antioxidation ability of this strain in different culture methods. Finally, the alleviating effect of highly active Lactobacillus plantarum on intestinal oxidative damage and the protective effect of epidermal cell barrier were discussed in order to provide a basis for the application and development of mixed microbial epigenetics.